A study on bank officers’ judgement in filtering money laundering risk: an experimental approach / Yusarina Mat Isa, Zuraidah Mohd Sanusi and Mohd Nizal Haniff - Mat Isa, Yusarina; Mohd Sanusi, Zuraidah; Haniff, Mohd Nizal (Faculty of Accountancy, 2016)
Exposure to money laundering risk is inherently alarming for the banks. Bank officers, who are the first line of defence in dealing with the customers, are undeniably facing difficulty to distinguish money launderers from other legitimate customers of the banks. Despite the existence of evaluation tools, bank officers’ judgement is pinnacle in assessing the exposure of money laundering risk. Based on behavioural decision theory, bank officers’ judgement is reckoned to be influenced by individual, contextual and organizational factors. This study aims to examine the influences of these behavioural factors on bank officers’ judgement through the operationalization of between-within-subjects experimental approach. Drawing upon 185 responses from bank officers in three banking institutions in Malaysia, the data were analyzed using Partial Least Squares of Structural Equation Modelling. By examining the factors in a controlled setting, it was found that individual factor (i.e. competency) acts as the anchor determinant in influencing bank officers’ judgement. Apart from the direct effect shown between competency and bank officers’ judgement, the study also provides evidence for the mediation effect of contextual factor (i.e. CDD task intensity) and moderation effect of organizational factor (i.e. regulatory supervision) on the relationship between competency and bank officers’ judgement. For a less explored area in the study of behavioural judgement, this study contributes in confirming the theoretical foundations underlying this research as well as adds value to the existing body of knowledge on money laundering risk. Practically, these findings are important in identifying the factors that matter for bank officers in assessing money laundering risk, as failure to correctly assess the risk implicates not only the banks but also the officers as gazetted in the Anti-Money Laundering, Anti-Terrorism Financing and Proceeds of Unlawful Act 2001. In this regard, understanding the behavioural factors influencing bank officers’ judgement is crucial in relieving bank officers from such liability.